Chromatographic methods for the bioanalysis of pyrethroid pesticides. (15th March 2016) - Gullick, Darren R.; Mott, Kyle B.; Bartlett, Michael G.
Abstract: Reliable analytical methods are needed for the determination of pyrethroid pesticides residues in biological tissues such as whole blood and plasma, meat, eggs, milk, brain, liver, and adipose tissue for monitoring of levels in livestock and for human risk assessment. A review of the current literature is given, with consideration to extraction techniques, sample preparation, and chromatographic approaches including both conventional and new technologies. Copyright © 2016 John Wiley & Sons, Ltd.